2010
DOI: 10.1103/physrevlett.104.146801
|View full text |Cite
|
Sign up to set email alerts
|

Band Engineering and Magnetic Doping of Epitaxial Graphene on SiC (0001)

Abstract: Using calculations from first principles we show how specific interface modifications can lead to a finetuning of the doping and band alignment in epitaxial graphene on SiC. Upon different choices of dopants, we demonstrate that one can achieve a variation of the valence band offset between the graphene Dirac point and the valence band edge of SiC up to 1.5 eV. Finally, via appropriate magnetic doping one can induce a half-metallic behavior in the first graphene monolayer. These results clearly establish the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…[12][13][14] The geometry of the graphene/SiC interface and the bonding that takes place in this region play a dominant role in the determination of the electronic properties of the active graphene layers: interface modifications can lead to a fine-tuning of the doping and band alignment of the system and provide a clear insight into the mechanisms of charge transfer and interface stability. 15 These findings, when placed in the more general context of ambient exposed graphene samples, provide the framework for the interpretation of the experimental results and a generalization to a universal behavior that should be expected in many other common situations. The goal of our study is to provide a quantitative and systematic evaluation of the impact of ambient exposure in epitaxial graphene samples.…”
Section: Methodsmentioning
confidence: 65%
“…[12][13][14] The geometry of the graphene/SiC interface and the bonding that takes place in this region play a dominant role in the determination of the electronic properties of the active graphene layers: interface modifications can lead to a fine-tuning of the doping and band alignment of the system and provide a clear insight into the mechanisms of charge transfer and interface stability. 15 These findings, when placed in the more general context of ambient exposed graphene samples, provide the framework for the interpretation of the experimental results and a generalization to a universal behavior that should be expected in many other common situations. The goal of our study is to provide a quantitative and systematic evaluation of the impact of ambient exposure in epitaxial graphene samples.…”
Section: Methodsmentioning
confidence: 65%
“…Figure 2(b) shows the band structures (left) without and (right) with the SOC for graphene/intercalated Bi/SiC. Not only does the gap not open, but the Bi also introduces an undesirable impurity state near the Fermi level, similar to light metal intercalations such as lithium 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Other computational details are the same as in Ref. 17. All calculations include 1 Na atom per 8 graphene carbon atoms in a computational unit cell that includes a carbon-rich buffer layer strongly bonded to the SiC surface but leaving several unsaturated dangling bonds.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 Theoretical studies demonstrated that modifications in the chemical composition of the buffer can lead to significant changes of the graphene bands, allowing for a fine tuning of the electronic structure of the system with band offsets up to 1.5 eV and even inducing magnetism of the graphene. 17 Alkali metal adsorption on graphene has been used extensively to study the effects of electron doping. Potassium deposition on graphene on SiC(0001) has enabled detailed studies of quasiparticles 18 and the discovery of plasmarons 19 in graphene.…”
Section: Introductionmentioning
confidence: 99%